THE ACTIVE AND PASSIVE SENTENCES IN STUDENTS’ NARRATIVE TEXT (Survey at Junior High School in Depok) - Mardina Salman; Supeno Supeno (INFERENCE: Journal of English Language Teaching, 2019)
The research was to find errors in using active and passive sentences in a narrative text. The research method was descriptive analysis using qualitative data. The procedures were identifying sentences, analysing, interpreting and concluding the result of the research. The writer only emphasized on 4 types of error in analysing the data which are omission, addition, misformation and misordering. The most errors are in misformation part which the wrong form of the structure or morpheme. The results are 1) there were 94 errors only in misformation of using active sentences. 2) In using passive sentence the most error is in misformation too, 69 (47.26%) of 146 (total error), next omission 47 (32.16%), misordering 18 (12.33%) and addition 12 (8.22%). The highest error is in misformation which happened because lacks of understanding in choosing the correct verb and arranging the correct passive form. While the lowest error is in addition, it happened because students only copy the active sentences.